2022
DOI: 10.3390/ijerph191610129
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Risk Factors for Electric Scooter-Related Crashes and Injury Crashes among Scooter Riders: A Two-Phase Survey Study

Abstract: Electric scooters (or e-scooters) are among the most popular micromobility options that have experienced an enormous expansion in urban transportation systems across the world in recent years. Along with the increased usage of e-scooters, the increasing number of e-scooter-related injuries has also become an emerging global public health concern. However, little is known regarding the risk factors for e-scooter-related crashes and injury crashes. This study consisted of a two-phase survey questionnaire adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 44 publications
2
7
0
Order By: Relevance
“…For example in Paris (France), Gioldasis et al (2021, p. 11) argues -without considering helmet use -that "male e-scooter riders are more likely to get engaged in risky behavior such as to drive after having consumed alcohol, after having consumed drugs, and to drive the e-scooter while using the smartphone". On the other hand, a survey of 210 e-scooter users in the US revealed that females are more likely to commit risky behaviors such as riding on a sidewalk (Tian et al, 2022). Our results are consistent with research that identi es no difference between male and female risky behavior (e.g., the speed of male e-scooter users was comparable to that of female users in Trondheim, Norway, Pazzini et al, 2022).…”
Section: Discussionsupporting
confidence: 88%
“…For example in Paris (France), Gioldasis et al (2021, p. 11) argues -without considering helmet use -that "male e-scooter riders are more likely to get engaged in risky behavior such as to drive after having consumed alcohol, after having consumed drugs, and to drive the e-scooter while using the smartphone". On the other hand, a survey of 210 e-scooter users in the US revealed that females are more likely to commit risky behaviors such as riding on a sidewalk (Tian et al, 2022). Our results are consistent with research that identi es no difference between male and female risky behavior (e.g., the speed of male e-scooter users was comparable to that of female users in Trondheim, Norway, Pazzini et al, 2022).…”
Section: Discussionsupporting
confidence: 88%
“…Traveling outside the bike path seems very dangerous, as also stated in other studies [28,52]. Strengthening and enhancing the visibility of bike path signage can effectively guide and inform both cyclists and other road users about the dedicated cycling infrastructure.…”
Section: Discussionmentioning
confidence: 69%
“…As for the right of way, some other countermeasures can be thought of, with the aim of improving as much as possible the already high safety conditions of e-scooters on bike lanes. Traveling outside the bike path seems very dangerous, as also stated in other studies [28,52]. Strengthening and enhancing the visibility of bike path signage can effectively guide and inform both cyclists and other road users about the dedicated cycling infrastructure.…”
Section: Discussionmentioning
confidence: 69%
“…For example, Gioldasis et al [28] analyzed data in Paris, France and found that male e-scooter riders were more likely to engage in risky behavior than female riders, including riding after drinking alcohol, using drugs and riding while using a mobile device. In contrast, a survey of 210 e-scooter users in the US found that females were more likely to engage in risky behaviors, such as riding on the sidewalk [31]. Meanwhile, a study in Norway reported no difference in risky behaviors between male and female riders when analyzing the speed of e-scooters [28].…”
Section: Trip Behaviormentioning
confidence: 94%